A Limit-Fed, High-Energy Diet Fed During the Growing Phase Does Not Negatively Affect Subsequent Feedlot Growth Performance or Carcass Merit Compared to Feeding a Traditional Roughage-Based Diet Ad Libitum During the Growing Phase - M. A. Scilacci; E. C. Titgemeyer; S. P. Montgomery; T. J. Spore; A. J. Tarpoff; T. G. O'Quinn; K. Montgomery; W. R. Hollenbeck; D. A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:The objective of this experiment was to compare the subsequent growth performance and carcass impacts of a high-energy diet limit-fed at 2.2% of body weight (BW) or a traditional roughage-based diet fedad libitumduring the growing phase. Study Description:Three hundred seventy crossbred heifers (initial BW = 496 ± 44 lb) previously used in a 90-day growing study at the Kansas State University Beef Stocker Unit were transported to a commercial feedlot (Pratt Feeders, Pratt, KS) for finishing where cattle were fed a common diet. The two backgrounding diets included: (1) 45 Mcal of net energy for gain (NEg) per 100 lb of dry matter (DM) fed forad libitumintake (45AL), or (2) 60 Mcal NEg per 100 lb of DM limit-fed at 2.2% of BW daily on a DM basis (60LF2.2). Both diets contained 40% of DM as Sweet Bran (Cargill Animal Nutrition, Blair, NE). Cattle were sorted by weight group (light or heavy) and backgrounding diet (45AL or 60LF2.2) and placed in one of four pens. Finishing growth performance and carcass characteristics were measured. Results:Heifers previously fed 60LF2.2 had greater morbidity (P<0.01) than heifers fed 45AL. No effect (P≥ 0.52) of backgrounding diet was observed in measured carcass characteristics. The Bottom Line:Although heifers previously limit-fed a high-energy diet during the growing phase appeared to have greater incidence of morbidity in the feedlot compared to heifers previously fed a traditional roughage-based diet, previous backgrounding diet had little or no carryover effect on feedlot growth performance or carcass characteristics measured.
Keywords: Limit feeding; growing cattle; finishing growth performance